PENGELOLAAN AIR TERJUN UMA ANYAR SEBAGAI DAYA TARIK WISATA ALAM DI DESA KEMENUH KABUPATEN GIANYAR - Ni Luh Putu Dina Purnamayanti; Astrid Krisdayanti; Ni Made Rai Kristina (UHN IGB Sugriwa Denpasar, 2023)
Uma Anyar Waterfall is one of the tourist attractions located in Kemenuh Village, Gianyar Regency. Uma Anyar Waterfall is known as a natural tourist attraction with natural and cultural potential that is interesting to be visited by local and foreign tourists. Seeing the tourism potential of Uma Anyar Waterfall, this management can be seen from the potential owned, management management and forms of community participation from the management of Uma Anyar waterfall. The theories used in this research are tourist destination theory, tourism management theory and participation theory. The method used in this research is a qualitative research method with a descriptive approach. The results showed that the potential of Uma Anyar Waterfall as a natural tourist attraction applies the concept of tourist destinations which includes Attraction, Amenities, Ancillary, Activity, Accessibilities and Available Package. The management of Uma Anyar Waterfall applies tourism management functions, namely, Planning, Organizing, Actuating, Controlling and Motivation, in addition to applying tourism management functions, local communities are also involved in managing Uma Anyar Waterfall. Community participation is divided into three (3) forms, namely: the form of ideas, the form of material and the form of labor that is actively involved. Recommendations that need to be applied in the Uma Anyar Waterfall tourist attraction are in terms of maximizing the management of facilities and infrastructure to support the development of Uma Anyar Waterfall in the future.